Predictors of entrepreneurial mindset among university students - Lope Pihie, Zaidatol Akmaliah; Arivayagan, Keetanjaly (ARC Publications Pvt., 2016)
Entrepreneurship Education (EE) is a learning process of developing learners’ skills and mindset, which creates a pathway to transform creative ideas into entrepreneurial action. In today’s tumultuous working environment, it is important for university students to gain entrepreneurship experience before graduating as many employers are seeking for students with entrepreneurial mindset. This is essential because students who have an entrepreneurial mindset are accountable for their own actions, brings new perspectives and youthful ideas into the workplace. Hence, this study explores the significant predictors of university student’s entrepreneurial mindset. This study endeavoured to answer the research questions through employing quantitative research method. The data was gathered by using simple random sampling, which consists of 366 university students. Findings indicated that University students have moderate level of entrepreneurial mindset and discovered that the level of self-entrepreneurial competencies was overall moderate level. The findings also found out a high correlation between self-entrepreneurial competencies with entrepreneurial mindset, followed by regression analyses revealed that risk propensity, creativity, planning and financial literacy are the significant predictors for university student’s entrepreneurial mindset. The results from this study provide in-depth insights about university students’ entrepreneurial mindset and create a delineate directions for further research and analyses. Implications and recommendations of the findings are presented in the paper.